2020
DOI: 10.1177/0959683620970255
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for early human habitation in the Nyingchi Region, Southeast Tibetan Plateau

Abstract: The lack of archaeological work has long impeded our understanding of prehistoric and historical human inhabitation and East-West interactions on the southeastern Tibetan Plateau (TP). In this study, we conducted a series of systematic archaeological investigations in the Nyingchi region, on the southeastern TP. We examined archaeological stratigraphies from 10 sites and collected charred seeds and charcoals for accelerator mass spectrometry (AMS) dating. The 26 radiocarbon dates show that the earliest inhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Although some new radiocarbon dates spanning 3000–2200 BP from Late Bronze Age sites along the Yarlung Tsangpo River (Wang et al, 2021) have been reported recently, the number of sites in this period is less than 4000–3000 BP (Figure 3c). This suggests there a decline in the significance of the trans-Himalayan routes or an absence of radiocarbon dating on these routes during the third millennium BP.…”
Section: Discussionmentioning
confidence: 91%
“…Although some new radiocarbon dates spanning 3000–2200 BP from Late Bronze Age sites along the Yarlung Tsangpo River (Wang et al, 2021) have been reported recently, the number of sites in this period is less than 4000–3000 BP (Figure 3c). This suggests there a decline in the significance of the trans-Himalayan routes or an absence of radiocarbon dating on these routes during the third millennium BP.…”
Section: Discussionmentioning
confidence: 91%
“…Even more intriguing is that both millet from the East and wheat/barley from the West made their way to the heart of the Tibetan Pleasure around 3400 cal BP (Gao et al, 2021). More new radiocarbon dates are published for southeast TP, showing that human activities started around the fifth millennium BP and peaked at cal 2700-2000 cal BP (Wang et al, 2021b). Both papers point out that agriculture performed a pivotal role in peopling the different parts of the Tibetan Plateau and this could not be achieved without the rise of the prehistoric Silk Road which cemented the East and the West.…”
Section: New Regions New Data and New Discoveriesmentioning
confidence: 99%
“…Fu 2001; d'Alpoim Guedes et al 2014; Chen et al 2015; Song et al 2017, 2021; Ren et al 2020a; Wang et al . 2020; Gao et al 2021; Tang et al . 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The origin and development of high-altitude agriculture on the Tibetan Plateau has attracted considerable interest during the last decade (e.g. Fu 2001;d'Alpoim Guedes et al 2014;Chen et al 2015;Song et al 2017Song et al , 2021Ren et al 2020a;Wang et al 2020;Gao et al 2021;Tang et al 2021). The Tibetan Plateau, with an average elevation of more than 4500m above sea level (asl), presents significant challenges for plant cultivation, as crops are required to tolerate hyperaridity, frost and salinity (Figure 1).…”
Section: Introductionmentioning
confidence: 99%